2010
DOI: 10.1016/j.bbmt.2010.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of CD4+CD25hiFOXP3+ Regulatory T Cells Has Diagnostic and Prognostic Value as a Biomarker for Acute Graft-versus-Host-Disease

Abstract: The relationship between regulatory T cells (Tregs) and acute graft-versus-host disease (GVHD) in clinical allogeneic bone marrow transplantation (BMT) recipients is not well established. We conducted a prospective analysis of peripheral blood Tregs as determined by the frequency of CD4+CD25hiFOXP3+ lymphocytes in 215 BMT patients. Autologous BMT patients (N=90) and allogeneic BMT patients without GVHD (N=65) had similar Treg frequencies, whereas allogeneic patients with GVHD (N=60) had Treg frequencies that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 31 publications
6
54
1
Order By: Relevance
“…In line with several previous studies in adult patients 19,20 and with one other pediatric study, 22 we found in our pediatric patient group a strong inverse correlation between FOXP3 þ T-cell frequencies early after HSCT and the development of alloreactive disease. This correlation also held true for the number of FOXP3 þ T cells within the grafts and alloreactivity.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In line with several previous studies in adult patients 19,20 and with one other pediatric study, 22 we found in our pediatric patient group a strong inverse correlation between FOXP3 þ T-cell frequencies early after HSCT and the development of alloreactive disease. This correlation also held true for the number of FOXP3 þ T cells within the grafts and alloreactivity.…”
Section: Discussionsupporting
confidence: 80%
“…As has previously been shown in adult patients, 20 pediatric patients who developed allo-reactive disease showed lower proportions of FOXP3 þ T cells before the development of alloreactive disease than patients who did not develop allo-reactive disease (P ¼ 0.01, Figure 1b). Owing to the low number of patients per subgroup, analysis according to stem cell source was not possible.…”
Section: Patient Characteristicssupporting
confidence: 57%
See 2 more Smart Citations
“…2,3 Several studies correlating Treg reconstitution and GVHD suggest that an imbalance between effector T cells and Tregs within the GVHD process may be more important than the absolute numbers of circulating Tregs. [4][5][6][7] However, Tregs are a heterogeneous population. Indeed, just as for conventional T cells, naive (nTreg) and memory Treg (mTreg) subsets have already been described.…”
Section: Introductionmentioning
confidence: 99%